SISTEM INFORMASI PERKUMPULAN WARGA KOTOGADANG (BUKITTINGGI) BERBASIS WEB - Hendwiko Kuncoro Putra; Dedi Irfan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
Computer technology has increasingly developed in its use. Along with the times, computers are widely used in various fields. One of the uses of technology is that it can be used as an information system for the community and those who need it. This information system does not only collect data from Kotogadang residents in various regions, but also provides up-to-date information about the situation occurring in the Kotogadang area in Bukittinggi and the activities that will be held in the Kotogadang area. So that Kotogadang residents who are in various regions can find out the information there. One method that is quite easy and efficient in the development of information system applications is to strengthen the relationship between fellow citizens of Kotogadang wherever located. Kotogadang citizen association information system is designed using the PHP (Hypertext Preprocessor) programming language with the CodeIgniter Framework, JavaScript, and using the MYSQL database. With this system can help Kotogadang residents in various regions in getting the latest information about meetings, sad news, and news of what is happening in the Kotogadang area in Bukittinggi. Keywords: Information System, PHP, CodeIgniter, MySQL.